2006
DOI: 10.1152/ajpcell.00409.2004
|View full text |Cite
|
Sign up to set email alerts
|

Distinct roles for ANG II and ANG-(1–7) in the regulation of angiotensin-converting enzyme 2 in rat astrocytes

Abstract: . Distinct roles for ANG II and ANG-(1-7) in the regulation of angiotensin-converting enzyme 2 in rat astrocytes. Am J Physiol Cell Physiol 290: C420 -C426, 2006. First published September 21, 2005; doi:10.1152/ajpcell.00409.2004.-Angiotensin-converting enzyme 2 (ACE2) is a homolog of ACE that preferentially forms angiotensin-(1-7) [ANG-(1-7)] from angiotensin II (ANG II). Incubation of neonatal rat cerebellar or medullary astrocytes with ANG II reduced ACE2 mRNA by ϳ60%, suggesting transcriptional regulation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
126
2
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 168 publications
(142 citation statements)
references
References 54 publications
13
126
2
1
Order By: Relevance
“…In contrast, AngII had no effect on ACE mRNA in A549 cells, demonstrating a differential regulation of the two enzymes by AngII. This finding is consistent with tests done in neonatal rat cerebellar and medullary astrocytes (33). Together, these findings demonstrated that AngII can magnify its effect in A549 cells through both decreased ACE2 production and increased AT1-R expression.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, AngII had no effect on ACE mRNA in A549 cells, demonstrating a differential regulation of the two enzymes by AngII. This finding is consistent with tests done in neonatal rat cerebellar and medullary astrocytes (33). Together, these findings demonstrated that AngII can magnify its effect in A549 cells through both decreased ACE2 production and increased AT1-R expression.…”
Section: Discussionsupporting
confidence: 91%
“…17,30 Although we recently demonstrated that central ACE2 was expressed primarily on neurons, 7 others reported astrocytic expression in vitro. 31 In addition, adenoviral transgenes do not integrate into the genome, therefore preventing random insertional mutagenesis. Although we did not assess inflammation resulting from virus injection, previous work using similar vectors and titers in the brain, 15,27 added to the lack of abnormal behavior in our infected mice, ruled out this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…In sharp contrast with these observations are several studies describing a complete or, less frequently, partial inhibition of Ang-(1-7) effects with A-779 , Ferreira et al 2001, Ferrario 2006, Gallagher et al 2006. In some studies a partial blockade was obtained with the AT 2 antagonist PD 123319 when a partial inhibition was also seen with A-779 and the B 2 receptor antagonist Hoe 140.…”
Section: Metabolic Actions Of the Ace2/ang-(1-7)/mas Axismentioning
confidence: 95%